Parent perceptions of the impact of the Paediatric Intensive Care environment on delivery of family-centred care. (February 2019) - Hill, Carrie; Knafl, Kathleen A.; Docherty, Sharron; Santacroce, Sheila Judge
Abstract: Objectives: To examine parent perception of how the physical and cultural environment of the paediatric intensive care unit impacted the implementation of family-centred care as outlined by the Institute for Patient and Family Centered Care. Research design: A qualitative descriptive design utilizing secondary analysis from a longitudinal study. Sixty-one interviews with three mothers and three fathers (31 interviews with mothers, 30 interviews with fathers) of infants with complex congenital heart defects treated in a paediatric intensive care unit were subjected to secondary analysis via content analysis. The previously completed individual interviews with parents took place at least monthly ranging from soon after birth of their infant to one year of age or infant death, whichever occurred first. Findings: The family-centred care core concepts of information sharing, participation, respect and dignity were present in parent interviews. Parents indicated that the physical and cultural environment of the pediatric intensive care unit impacted their perceptions of how each of the core concepts was implemented by clinicians. The unit environment both positively and negatively impacted how parents experienced their infant's hospitalisation. Conclusion: In the paediatric intensive care unit, family centred care operationalised as policy differed from actual parent experiences. The impact of the physical and cultural environment should be considered in the delivery of critical care, as the environment was shown to impact implementation of each of the core concepts.